2014
DOI: 10.1007/s13204-014-0342-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH values on nanostructured Ni–P films

Abstract: Electroless Ni-P films were deposited on mild steel substrate and sodium dihydrogen phosphite was used as a reducing agent. Temperature and pH of the bath were maintained at 90°C and 6.86 to 10.86 respectively. The Ni-P film deposited samples were characterized by FE-SEM to know the surface and cross-section morphology of the film and the phases present were examined by X-ray diffraction. The chemical composition of the electroless Ni-P films was determined by EDS analysis. The thickness of the film was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Near the area with high H + concentration, the deposition rate is low due to the slow formation and growth of crystal nucleus, resulting in thin coating and no significant improvement in hardness. Similar situations have been reported in a similar pH bath [24,25]. Besides, it has been pointed out that the pH of the plating solution has an effect on the P content of the coating, that is, the hardness of the coating increases with the decrease of P content [26].…”
Section: Effect Of Ph Value On Microhardness Of Compositesupporting
confidence: 78%
“…Near the area with high H + concentration, the deposition rate is low due to the slow formation and growth of crystal nucleus, resulting in thin coating and no significant improvement in hardness. Similar situations have been reported in a similar pH bath [24,25]. Besides, it has been pointed out that the pH of the plating solution has an effect on the P content of the coating, that is, the hardness of the coating increases with the decrease of P content [26].…”
Section: Effect Of Ph Value On Microhardness Of Compositesupporting
confidence: 78%
“…All the coatings showed the typical nodular growth with cauliflower-like endings randomly distributed on the surface showing differences in size and nodules distribution. Among the different factors able to impact surface topography, pH and the nature and concentration of complexing agents are the most important ones and, presumably, they act together (i.e., mixed effect) on surface topography of electroless nickel coatings [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electroless Ni-P deposition reaction can occur in an alkaline or acid environment. To study the autocatalytic deposition of Ni accompanied by P incorporation in the film, it is necessary to know the effect of the operating parameters and bath chemistry on the deposition rate and the quality of the deposits, such as the substrate nature [16], pH [17,18], plating temperature [19], stirring [20], light [21], stabilizers [22], complexing agent [23], and additives [24]. In order to perform deposition of electroless Ni-P, the substrate surface needs to be preactivated and presensitized.…”
Section: Introductionmentioning
confidence: 99%
“…However, the deposition rates decreased with the increase in sodium citrate. Rahman and Jayaganthan [18] studied the effect of pH on electroless Ni-P films on the surface of mild steel and concluded that the Ni content increased with increasing pH. Moniruzzaman and Roy [17] reported that electroless Ni-P coating was produced on carbon steel and polypropylene substrates and pointed out that the coating of good appearances was obtained in the pH ranges between 5.5 and 12.5 on carbon steel and between 8.5 and 12 on the polypropylene.…”
Section: Introductionmentioning
confidence: 99%